Neural correlates of sensory preconditioning: a preliminary fMRI investigation - Yu, Tao; Lang, Simone; Birbaumer, Niels-Peter; Kotchoubey, Boris (Human brain mapping, 2014)
Sensory preconditioning (SPC; also known as behaviorally silent learning) consists of a combination of two neutral stimuli, none of which elicits an unconditional response. After one of them is later paired with an unconditional stimulus (US), the other neutral stimulus also yields a conditional response although it has never been paired with the US. In this study, an event-related functional magnetic resonance imaging (fMRI) paradigm was used to specify brain regions involved in SPC. The results demonstrated that SPC was associated with significant changes in activity of several regions, notably, the left amygdala, the left hippocampus, the bilateral thalamus, the bilateral medial globus pallidus, the bilateral cerebellum, the bilateral premotor cortex, and the bilateral middle frontal gyrus. This is a first effort to use fMRI to examine the effects of SPC on brain activation. Our data suggest that there is a distributed network of structures involved in SPC including both cortical and subcortical regions, therefore add to our understanding of the neural mechanisms underlying the ability to associative learning.
Published online 1 March 2013
Gesehen am 18.08.2020